War-Torn Eritrean Economy: Some Issues and Trends. - Rena, Ravinder (2007)
The three decades of armed struggle, the subsequent drought, and deliberate policies of neglect and mismanagement by the last two regimes in Eritrea made the growth of the Eritrean economy practically impossible. After independence, the country achieved a steady growth for some years. However, due to the border conflict with Ethiopia, the economy was characterised by severe macroeconomic imbalances and unusually high level of public expenditure. Poverty and inflation also increased manyfold. Both domestic and external public debts reached unsustainable levels. An attempt is made in this paper to delve into some important trends of the Eritrean economy before and after 1998. The paper highlights some of the key economic issues like education, health, infrastructure, unemployment and poverty, and provides some concluding observations.